One Extra Copy of lon Gene Causes a Dramatic Increase in Actinorhodin Production by Streptomyces coelicolor A3(2) - Demir, Zeynep; Bayraktar, Asli; Tunca, Sedef (Springer, 2019)
ATP-dependent Lon protease plays important roles in different physiological processes, including cellular differentiation of the bacteria and is a part of an important stress response regulon (HspR/HAIR). In Streptomyces, biosynthesis of secondary metabolites starts with cellular differentiation and stress is one of the factor that affect metabolite production. To clarify the effect of Lon protease on secondary metabolite production, we constructed a recombinant strain of Streptomyces coelicolor A3(2) that has one extra copy of lon gene with its own promoter and transcriptional terminator in its genome. Expression of lon gene in the recombinant strain was determined by quantitative real time (RT-qPCR). Actinorhodin and undecylprodigiosin production of the recombinant cell was measured in liquid R2YE and it was found to produce about 34 times more actinorhodin and 9 times more undecylprodigiosin than the wild-type at 168h of growth. Development of stable Streptomyces strains capable of producing high amounts of secondary metabolites is valuable for biotechnology industry. One extra copy of lon gene is enough to boost antibiotic production by S. coelicolor A3(2) and this change do not cause any metabolic burden in the cell.
Keywords: Atp-Dependent Protease; Amino-Acid Starvation; Escherichia-Coli; Antibiotic Production; Inorganic Polyphosphate; Quantitative Pcr; Rna-Polymerase; In-Vitro; Expression; Degradation